2016
DOI: 10.1186/s12864-016-3191-3
|View full text |Cite
|
Sign up to set email alerts
|

Prepartum body condition score and plane of nutrition affect the hepatic transcriptome during the transition period in grazing dairy cows

Abstract: BackgroundA transcriptomic approach was used to evaluate potential interactions between prepartum body condition score (BCS) and feeding management in the weeks before calving on hepatic metabolism during the periparturient period.MethodsThirty-two mid-lactation grazing dairy cows of mixed age and breed were randomly allocated to one of four treatment groups in a 2 × 2 factorial arrangement: two prepartum BCS categories [4.0 (thin, BCS4) and 5.0 (optimal, BCS5); based on a 10-point scale], and two levels of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…The present study demonstrated that M-eff calves had greater enrichment of key metabolites involved in energy-generating pathways such as citric acid cycle, gluconeogenesis, biotin metabolism, pyruvate metabolism, fructose and mannose degradation, and nicotinate and nicotinamide metabolism [26][27][28], potentially enhancing the supply of energy to the calf. Furthermore, the induction of metabolic pathways for amino acid (alanine metabolism), vitamin (biotin metabolism) and fatty acid (arachidonic acid metabolism) metabolism at birth in M-eff calves also could have benefitted hindgut development and function during the preweaning period [29].…”
Section: Hindgut Microbiome and Metabolome At Birth Energy Supplymentioning
confidence: 65%
“…The present study demonstrated that M-eff calves had greater enrichment of key metabolites involved in energy-generating pathways such as citric acid cycle, gluconeogenesis, biotin metabolism, pyruvate metabolism, fructose and mannose degradation, and nicotinate and nicotinamide metabolism [26][27][28], potentially enhancing the supply of energy to the calf. Furthermore, the induction of metabolic pathways for amino acid (alanine metabolism), vitamin (biotin metabolism) and fatty acid (arachidonic acid metabolism) metabolism at birth in M-eff calves also could have benefitted hindgut development and function during the preweaning period [29].…”
Section: Hindgut Microbiome and Metabolome At Birth Energy Supplymentioning
confidence: 65%
“…Therefore, Gln + Glu supplementation may be an important nutritional resource for lactating mares, as has been proposed for dairy cows and pigs [1,11,16], possibly limiting muscle catabolism and helping them to maintain fat-free body mass. This is important to regulate the female reproductive cycle [27], especially that of pasture-fed females, since the quality and quantity of nutrients in grass may vary throughout the year and animals may use their protein and fat stores to support gestation and lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Pomin (2015) concluded that GAG displays anti-in ammatory functions by activating leukocyte rolling along the endothelial surface of inflamed sites and also regulating chemokine action on leukocyte guidance, migration and activation [26]. The study of Vailati-Riboni et al (2016) in transition cows demonstrated that feeding at 125% of nutrient requirements activated hepatic GAG synthesis pathways in underconditioned cows, while it inhibited it in optimally-conditioned cows [27]. Thus, it was suggested that overfeeding of fatter cows may decrease the synthesis of anti-in ammatory compounds and consequently induce some detrimental effects [27].…”
Section: Low-quality Forage Inhibited Glycan Biosynthesis and Metabolismmentioning
confidence: 99%